Analisis Pengaruh Penambahan Cangkang Keong Pada Kualitas Paving Block Berbahan Dasar Limbah Plastik - Izzan Faza, Aufa Muhammad; Akmal Nashrullah, Muhammad Aufa; Dwi Atmoko, Indrato; Widayoko, Agus (SMA Trensains Muhammadiyah Sragen, 2024)
Plastic waste is a serious problem that must be addressed immediately. Indonesia produces 36 million tons/year of waste, of which 17.9% is plastic according to the National Waste Management Information System (SIPSN). In fact, plastic waste is a type of waste that is difficult to decompose (nonbiodegradable). Rice snail is one of the pests of rice plants in Indonesia. Its utilization is still limited among the community. Whereas snail shells contain calcium carbonate by 86.86%. The purpose of this study was to determine the effect of conch shells on the quality of plastic-based paving blocks. This type of research is descriptive with a quantitative approach. The description focuses on product manufacturing and testing. Data collection with experiments and literature studies. Indicators of product effectiveness if all tests are met. The analysis technique uses simple statistical calculations. The results of the effectiveness test show that conch shells affect the quality of plastic paving blocks, which will strengthen the paving blocks and increase water absorption. Based on the results of existing research, it can be concluded that the addition of conch shells to plastic-based paving blocks makes the paving blocks have greater compressive strength. In addition, conch shells also affect the absorbency of paving blocks. Suggestions for future researchers are to use a plastic melting tool to get the maximum plastic melt and find the correct level of conch shells so that the paving block has a higher compressive strength.